P521 Correlation between physician disease assessment in Ulcerative Colitis and burden of disease: ICONIC 2-year data of 120 patients in Turkey. (27th May 2021) - Sezgin, O; Atug, O; Gonen, C; Can, G; Duman, A E; Erzin, Y Z; Yurci, M A; Alkim, C; Unal Ozcelik, N G; Yildirim, B; Kayacetin, E; Beyazit, Y; et al.
Abstract: Background: Ulcerative colitis (UC) is a chronic inflammatory bowel disease (IBD), and the overall burden is increasing at the global level. Differences in perceptions of UC-related burden may highlight dramatic degree insufficient patient-physician communication. ICONIC is a prospective, non-interventional, observational study assessing disease burden in adults with UC using Pictorial Representation of Illness and Self Measure (PRISM). The local results of ICONIC study for Turkey are presented. Methods: Patients aged ≥18 years with early UC (diagnosed ≤36 months) were enrolled. At baseline and every 6 months, patient and physician reported outcomes were collected using PRISM, the Simple Clinical Colitis Activity Index (SCCAI and P-SCCAI), The Rating Form of IBD Patients' Concerns (RFIPC), the Short Inflammatory Bowel Disease Questionnaire (SIBDQ), and the Patient Health Questionnaire-9 (PHQ-9). Correlations between the patient assessed PRISM and other measurement tools were evaluated with Pearson correlation coefficient. Results: One hundred and twenty patients were included (77 [64.2%] female; mean age 35.2 years). Physician-assessed disease severity was: severe 23 [19.2%], moderate 42 [35.0%], mild 40 [33.3%], in remission 15 [12.5%]. The mean ± SD physician- and patient-assessed PRISM scores were 4.8 ± 2.3 cm (range: 0.0–9.0) and 4.1 ± 2.6 cm (range: 0.0–8.5) at baseline and increased to 6.1 ± 2.3 cm (range: 0.1–8.5) and 5.5 ± 2.7 cm (range: 0.0–9.3) at the final visit, respectively, indicating an improvement in the perceived disease burden. The mean values of physician-SCCAI and P-SCCAI were 3.8 ± 3.5 and 5.5 ± 4.3 at baseline and decreased to 1.4 ± 2.5 and 2.7 ± 3.2 at the final visit, respectively, showing a decrease in disease activity. At baseline, the RFIPC and PHQ-9 values were 2.7 ± 1.7 and 8.0 ± 5.5 and decreased to 2.2 ± 2.0 and 5.2 ± 4.5 at the final visit, respectively. Patient-assessed SIBDQ was 43.8 ± 14.5 at baseline and increased to 54.0 ± 13.0 at the final visit. The strongest correlation of patient-assessed PRISM was with the physician-assessed PRISM (Spearman rho = 0.69, p<0.0001), followed by SCCAI (rho = -0.56, p<0.0001). Differences between physician- and patient-assessed PRISM scores were statistically significant (baseline: p=0.0010 vs. final visit: p=0.0206), highlighting an underestimation of patient's suffering by physicians. Conclusion: In the Turkish ICONIC sub-study, majority of patients on treatment showed improved outcomes during the follow-up period. A moderate correlation between patient-assessed PRISM and other measurement instruments represents that PRISM may be used as surrogate marker for patient suffering.